WhatsApp and Gynecologist-Patient Interaction: Development and Validation of a Questionnaire to Assess the Stress Perceived by the Doctor - Veiga, Melissa Gonzalez; Felizi, Rogério Tadeu; Fernandes, César Eduardo; Oliveira, Emerson (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2022)
Objective Construction and validation of the WhatsApp Stress Scale (WASS), a questionnaire designed for physicians that measures how the use of smartphones and related software communication applications affects the quality of life of gynecologists who use this tool to communicate with patients.Methods The present cross-sectional observational study analyzed 60 gynecologists according to weekly WhatsApp usage time for communication with patients and compared the data with the perception of the doctor on the use of this virtual interaction as a stressor. Physicians were equally divided into three groups: < 2 hours, 2 to 5 hours, and > 5 hours. The authors created a questionnaire in Likert scale format. The study proceeded in three phases: development of the questionnaire items, pretesting, constructing, and validity and reliability testing using factor analysis, Cronbach α coefficient, and paired t-test.Results A 9-item instrument using a 5-point Likert scale was created and administered to the participants in 3 different times: T0, T1 (15 minutes after the end of T0), and T2 (15 days later). All questionnaire items possessed adequate content validity indices and the internal consistency of the instrument was satisfactory (Cronbach α 0.935; 95% confidence interval [CI]: 0.744–0.989; p = 0.0001). No statistically significant differences were observed in the responses between the rounds of testing, indicating good test-retest reliability. A positive association between the high frequency of WhatsApp usage for communication with patients and the stress perceived by the doctor was shown.Conclusion The WASS is a valid and reliable instrument for assessing the use of messaging applications to communicate with patients as a stressor perceived by gynecologists.
Keywords: mobile applications; occupational stress; physician-patient relations; smartphone; questionnaire